Estetika Arsitektur Dalam Perspektif Teknologi Dan Seni - Utomo, Tri Prasetyo (Pendhapa, 2009)
Philosophical Aesthetics here is considered to center on these latter-day developments. Some aesthetic effects available in architecture, technology, and visual arts include tonal variation, juxtaposition, repetition, field effects, symmetry/asymmetry, perceived mass, subliminal structure, linear dynamics, tension and repose, pattern, contrast, perspective, 3 dimensionality, movements, rhythm, unity, and proportion. An aesthetic experience is just the experience of aesthetic properties and formal relations of a work. But this leads to problems concerning the attribution of aesthetic properties and whether we detect them or they are merely projected. Carroll suggests that the mere fact that we disagree about the attribution of aesthetic properties gives us at least some minimal reasons to presume that aesthetic properties are objective. Our response to art is unique and not precisely intellectual; beauty and perfection that we find in works of art do not consist of concepts but sense impressions. Key words : aesthetics, architecture, technology, art.